Consequence Analysis of a Station Blackout in Brazilian Nuclear Power Plant Angra 2 - Andre S Aguiar; Seung Min Lee; Gaianê Sabundjian (Brazilian Journal of Radiation Sciences)
The article consists, through a Severe Accident, evaluating the impact of radionuclides released into the atmosphere in the vicinity at Nuclear Power Plant. The source term used in present work is obtained by means of proportionality between Angra 1 and Angra 2. That is, the source term of Angra 2 is calculated based on its activity estimated from numbers of fuel pellets of both power plants and the already known activity of Angra 1. This calculation resulted in total activity of Angra 2 equivalent to 146.18% of activity of Angra 1. The results indicate that for severe accident scenarios, the protective measures to be adopted will be general emergency; and the impact area, which currently has a distance of 5 km, would become greater than this value.